Effectiveness of omega-3 fatty acids in the management of hypertriglyceridemia: a multi-centre retrospective study - Gondane, Ajitkumar A.; Vaidya, Pooja H.; Pawar, Dattatray B.; Sharma, Akhilesh D. (International Journal of Research in Medical Sciences, 2026)
Background: Hypertriglyceridemia is increasingly prevalent in India and represents a major contributor to atherosclerotic cardiovascular disease and overall cardiometabolic risk. Although large global trials have demonstrated the triglyceride-lowering efficacy of Omega-3 fatty acids (O3FA), real-world evidence regarding their effectiveness, safety, and prescribing patterns in the Indian population remains scarce. This study aimed to evaluate the real-world effectiveness, safety, and utilization patterns of O3FA therapy in Indian patients with hypertriglyceridemia. Methods: This retrospective, multicentre observational study analyzed medical records of patients diagnosed with hypertriglyceridemia who were prescribed O3FA between January 2023 and April 2024 across multiple healthcare centers in India. Demographic details, treatment duration, lipid parameters, glycemic indices, and adverse events were assessed. Results: A total of 447 patient records were included in the analysis. The majority were male (80.3%), with a mean age of 49.5 years. Patients received one O3FA capsule daily for a mean duration of 2.09 months. Statistically significant and clinically meaningful improvements were observed in lipid parameters: triglycerides decreased by 113.42 mg/dl, total cholesterol by 75.99 mg/dl, LDL-C by 49.15 mg/dl, and VLDL by 13.99 mg/dl, while HDL-C increased by 16.47 mg/dl (p<0.001 for all). Glycemic control also improved, with reductions in fasting blood glucose (−24.79 mg/dl), postprandial glucose (−10.17 mg/dl), and HbA1c (−0.94%). Only four patients reported mild gastrointestinal adverse events, and no serious adverse events were documented. Conclusions: O3FA therapy demonstrated significant improvements in lipid and glycemic parameters with an excellent safety profile, reinforcing its role as an effective and well-tolerated cardiometabolic intervention in routine Indian clinical practice.